Zapobieganie nieprawidłowościom w rozwoju artykulacji u dzieci w wieku niemowlęcym i poniemowlęcym - Gacka, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The development of speech, including articulation, begins at birth, whereas its biological foundations are shaped already during the foetal development. The acquisition of linguistic competence (including phonetic and phonological) is determined by various factors. The article is dedicated to the preventive care in regard to speech disorders of children. The author primarily focuses on the primary activities of speech/articulation (articulation is one of the aspects of speech, and the primary activities of speech may be considered, simultaneously, as primary in comparison to articulation). The article presents activities that prevent the occurrence of articulation development disorders, directed at infants and post-infancy children.